Zastosowanie mnożnika EBITDA w wycenie kandydata do przejęcia - Rutkowski, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
EBITDA multiples are commonly used in the valuation processes of Polish public and private companies. EBITDA multiple approach should be applied very carefully. Research presented in this paper shows a significant relationship between value of the companies and value of EBITDA multiples on the Polish capital market. Multiple valuation approach needs in-depth analysis of sector particularity and analysis of capital structure of merged companies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 433-446